In search of Florentine civic humanism : essays on the transition from medieval to modern thought. - Baron, Hans, 1900-1988 (Princeton legacy library., 1988)
Hans Baron's Crisis of the Early Italian Renaissance is widely considered one of the most important works in Italian Renaissance studies. Princeton University Press published this seminal book in 1955. Now the Press makes available a two-volume collection of eighteen of Professor Baron's essays, most of them thoroughly revised, unpublished, or presented in English for the first time. Spanning the larger part of his career, they provide a continuation of, and complement to, the earlier book. The essays demonstrate that, contemporaneously with the revolution in art, modern humanistic t.